Kilpailu, ikääntyminen ja investointien vähäisyys - Aki Kangasharju; Jyrki Ali-Yrkkö; Heli Koski; Tero Kuusi (The Research Institute of the Finnish Economy (ETLA), 2021)
– This report discusses factors that have caused a decrease in tangible investments in machinery and equipment, and intangible assets in Finland. A decline in the R&D investments of the electronics industry practically entirely explains a decrease in investments in Finland, which has prolonged the recovery from the collapse of productivity growth during the financial crisis. The corporate sector, which accounts for most investments, also contracted so much during the financial crisis relative to the rest of the economy that the aggregate productive investments remained lower than before. Companies' investments in relation to their value added did not decrease, however. The main reason for the collapse of the electrotechnical industry is the loss of the Symbian mobile phone operating system in global competition. Together with that, profitability collapsed, and no new R&D investment opportunities of a similar size were found. However, companies should not avoid competition, and instead, the competitive environment, in general, acts as an investment incentive for companies. Developments in the 2010s also highlight the importance of international competition and international trade agreements. The decline in the working-age population that began at the same time as zero growth does not explain the collapse in investments, but it has to do with their slow recovery.
Keywords: E22; L16; O52; P45; 330; Investments; Competition; Competitiveness; Structural change; Population ageing